2022
DOI: 10.3390/cryst12040552
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Color-Adjustable Europium and Terbium Co-Doped Strontium Molybdate Phosphors Synthesized at Room Temperature Applied to Flexible Composite for LED Filter

Abstract: In this study, terbium and europium rare-earth ions were single-doped and co-doped to synthesized SoMoO4 phosphor at room temperature. The samples prepared synthesized crystalline SrMoO4 powder by the co-precipitation. Samples had a tetragonal structure in XRD analysis and d(112) spacing was changed by rare-earth doping. As the amount of rare earth added increased, a secondary phase appeared, and the structure changed. The synthesized SrMoO4:Tb3+ phosphors showed a green light emission at 544 nm under 287 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…One of the best examples of these is the molybdate of a powellite structure that naturally occurs as CaMoO 4 , adopting a scheelite-type tetragonal phase (space group I 4 1/a, Z = 4). Molybdates are of particular interest due to their outstanding luminescence properties, which are applied in gas detectors [8,9], optical devices [10][11][12][13][14][15], and scintillation detectors [16][17][18][19]. Different synthesis and processing techniques lead to changes in structural properties, which affect the material properties and comprise a motivating factor in the investigation of the formation of SrMoO 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the best examples of these is the molybdate of a powellite structure that naturally occurs as CaMoO 4 , adopting a scheelite-type tetragonal phase (space group I 4 1/a, Z = 4). Molybdates are of particular interest due to their outstanding luminescence properties, which are applied in gas detectors [8,9], optical devices [10][11][12][13][14][15], and scintillation detectors [16][17][18][19]. Different synthesis and processing techniques lead to changes in structural properties, which affect the material properties and comprise a motivating factor in the investigation of the formation of SrMoO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques are used to synthesize SrMoO 4 , including the Czochralski method [13], coprecipitation [7,18], traditional solid-phase reactions [12,23], sol-gel synthesis [9], hydrothermal synthesis [17], and microwave hydrothermal synthesis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the emission wavelength of phosphors used in various types of light devices can vary depending on the type and concentration of the doped rare earth ions, the sintering temperature, crystal grain size, excitation wavelength, and synthesis conditions [10][11][12][13]. In particular, the main emission wavelength of the rare earth ions is determined by competition between electric dipole transitions and magnetic dipole transitions.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Thus, various lanthanide-doped luminescent nanoparticles are reported in the literature. Most common hosts that have been used for preparing such nanoparticles are NaBi(MoO 4 ) 2 , 11 SrWO 4 , 12 BaMoO 4 , 13 BaWO 4 , 14 CaMoO 4 , 15 SrMoO 4 , 16 Ca 3 Bi(PO 4 ) 3 , 17 CaAl 2-Si 2 O 8 , 18 La(PO 4 ) 19 and YPO 4 . [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Out of these hosts, yttria (YPO 4 ) has been widely used as it is isostructural to the lanthanide phosphates (LnPO 4 ).…”
mentioning
confidence: 99%
“…9,10 Thus, various lanthanide-doped luminescent nanoparticles are reported in the literature. 11–31 Most common hosts that have been used for preparing such nanoparticles are NaBi(MoO 4 ) 2 , 11 SrWO 4 , 12 BaMoO 4 , 13 BaWO 4 , 14 CaMoO 4 , 15 SrMoO 4 , 16 Ca 3 Bi(PO 4 ) 3 , 17 CaAl 2 Si 2 O 8 , 18 La(PO 4 ) 19 and YPO 4 . 20–34…”
mentioning
confidence: 99%